1992
DOI: 10.1002/macp.1992.021930409
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrochromic stability of polyaniline in polyaniline‐matrix polymer composite films in aprotic medium

Abstract: Electrochromic behavior and stability in aprotic medium of polyaniline composite films prepared by chemical oxidative polymerization at gadliquid interface were investigated. The results are compared with chemically and electrochemically snythesized polyaniline homogeneous films. The polyaniline composite films show almost the same electrochromic behavior as the homogeneous films. The behavior is due to a two-step oxidation mechanism, which is different from that in aqueous medium, especially in the second oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…For large-area device applications, alternative methods (e.g., solution-cast films, 36 polymer dispersions, 21 composites, 37,38 and in situ polymerization 39 ) have been employed. Generally, the electrochemical approach leads to better adhesion of the polymer film onto the conductive substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For large-area device applications, alternative methods (e.g., solution-cast films, 36 polymer dispersions, 21 composites, 37,38 and in situ polymerization 39 ) have been employed. Generally, the electrochemical approach leads to better adhesion of the polymer film onto the conductive substrate.…”
Section: Introductionmentioning
confidence: 99%
“…40 For example, electrochemically deposited poly(diphenylbenzidine) films have been reported to be easily detached from the ITO electrode upon potential cycling. 30 Furthermore, silanized polyaniline, 41 amino-silanized glass, 39 and conducting polymer composites 38,[42][43][44][45][46] have been employed to promote the surface adhesion of electrodeposited and solution-cast films. For example, Wei et al have recently demonstrated the durability of large-area electrochromic coatings based on composites of polyaniline and polyacrylatesilica hybrid sol-gel materials.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, conducting polymers are not suitable for uses as simple electrical conductors at the present, and their utility as practical industrial materials have been investigated for applying the property changes by the doping-dedoping processes. For example, changes of their chemical potentials are applied to materials for batteries, 6 changes of their optical properties are applied to materials for displays, 7 and changes of their electrical and magnetic properties are applied to materials for sensors 8 and memories. 9 In addition, changes of their electrochemical properties are proposed for their application to novel functional separation membranes that can dynamically control the ionic permeability by an external operation like applying potential.…”
Section: Introductionmentioning
confidence: 99%
“…This means the formation of a "polaron band" 36) in other terms. As the potential is raised more positive, the absorption at 420 nrn turns to decrease at 0,3 V, and the absorption at 800 nm shifts to lower wavelength above 0,7 V. It was presumed from X-ray photoelectron spectroscopy (XPS) in my previous report 19) that the shift of the absorbance at 800 nm is due to formation of the quinonediimine cation structure of polyaniline. These electrochromic behaviors point to a two-step oxidation process.…”
Section: Polyion Complex (Pic) Matrix Firmsmentioning
confidence: 95%